2020
DOI: 10.1177/1350508420966743
|View full text |Cite
|
Sign up to set email alerts
|

The organizational inclusion turn and its exclusion of low-wage labor

Abstract: As most scholarly work on the conceptualization of organizational inclusion seems to be implicitly based on contexts of high-wage labor, this article investigates whether the common themes of organizational inclusion as identified by Shore et al. (2018) also align with the low-wage labor context. Our respective analysis identifies several mismatches between the current conceptualizations of organizational inclusion and the needs and interests of low-wage workers. Consequently, we offer suggestions for adapting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 98 publications
1
19
1
2
Order By: Relevance
“…Bowie, 2017). The recently proposed stakeholder governance perspective (Amis et al, 2020b), economic value creation by stakeholders (Bapuji et al, 2018), economic-social-economic cycle of inclusion (Fujimoto & Uddin, 2021), and inclusion concepts for lowwage workers (van Eck et al, 2021) encourage corporate leaders and other stakeholders to prioritize the interests of most exploited stakeholders in order to meet their economic needs. The key stakeholders prioritizing fair employment practices at low-wage workplaces may reverse the hierarchical discriminatory trends within the workforce, which are particularly imposed on female workers in the patriarchal society (cf.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bowie, 2017). The recently proposed stakeholder governance perspective (Amis et al, 2020b), economic value creation by stakeholders (Bapuji et al, 2018), economic-social-economic cycle of inclusion (Fujimoto & Uddin, 2021), and inclusion concepts for lowwage workers (van Eck et al, 2021) encourage corporate leaders and other stakeholders to prioritize the interests of most exploited stakeholders in order to meet their economic needs. The key stakeholders prioritizing fair employment practices at low-wage workplaces may reverse the hierarchical discriminatory trends within the workforce, which are particularly imposed on female workers in the patriarchal society (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The past study also reported the managerial approach to addressing the individual needs of operative workers as being a key dimension of non-rank sensitive inclusion, breaking the norm of exploitation and simultaneously building symbolic and emotional connections among the workers (Holck, 2017;Janssens & Zanoni, 2008). The recent research has also verified the importance of non-task oriented involvement for building social relationships for greater inclusion of the low-wage workers in workplaces (van Eck et al 2021). Thus, we predicted that managerial consideration as social resources for the workers would stir a non-rank sensitive inclusion, which would, in turn, enhance workers' psychological well-being.…”
Section: Managerial Consideration Non-rank Sensitive Inlcusion and Li...mentioning
confidence: 96%
See 3 more Smart Citations